2008
DOI: 10.1007/s00221-007-1258-8
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial magnetic stimulation and brain atrophy: a computer-based human brain model study

Abstract: This paper is aimed at exploring the effect of cortical brain atrophy on the currents induced by transcranial magnetic stimulation (TMS). We compared the currents induced by various TMS conditions on several different MRI derived finite element head models of brain atrophy, incorporating both decreasing cortical volume and widened sulci. The current densities induced in the cortex were dependent upon the degree and type of cortical atrophy and were altered in magnitude, location, and orientation when compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 65 publications
1
62
0
2
Order By: Relevance
“…Theodore et al have shown that an effect on spikecount can be obtained more reliably in patients with neocortical than in patients with deep foci (Theodore et al 2002). This is well explained by the fact that the magnetic field is reaching only a depth of about 2-4 cm within the brain tissue (Wagner et al 2008). However, patient #4 was the only patient with a rather deep epileptic focus (mesial temporal due to hippocampus sclerosis), but the only one who positively responded to inhibitory rTMS.…”
Section: Discussionmentioning
confidence: 94%
“…Theodore et al have shown that an effect on spikecount can be obtained more reliably in patients with neocortical than in patients with deep foci (Theodore et al 2002). This is well explained by the fact that the magnetic field is reaching only a depth of about 2-4 cm within the brain tissue (Wagner et al 2008). However, patient #4 was the only patient with a rather deep epileptic focus (mesial temporal due to hippocampus sclerosis), but the only one who positively responded to inhibitory rTMS.…”
Section: Discussionmentioning
confidence: 94%
“…There is, however, sufficient evidence to suggest that the current used here can reach the brain. The bone is the structure with highest resistance, and has to be considered primarily when stimulating the head electrically (Wagner et al, 2008). In fact, high bone resistance was the reason why TMS replaced pulsed electrical stimulation in 1985 (Barker et al, 1985) and thereby could avert painful stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that cathodal stimulation of the unaffected hemisphere will cause a suppression of activity locally, allowing for the transcallosal disinhibition of the affected hemisphere, thereby increasing neuroplastic response to repair itself [17]. This same mechanism has been proposed for the improvement of neurocognitive deficits in stroke patients; specifically in task related functions [18], as well as, memory and affective complications [19][20][21]. These results, though minimal, are statistically significant in demonstrating that modulation of ipsilesional activity can improve motor recovery, likely by promoting plastic reorganization of spared cortex.…”
Section: Transcranial Magnetic Stimulation/transcranial Direct Currenmentioning
confidence: 96%
“…A review examining DBS with motor and sensory cortical stimulation examines all recent prospective studies examining long-term outcomes in patients and advocate that DBS is superior to motor cortical stimulation for refractory pain syndromes and may be more appropriate than sensory cortical stimulation for certain pain etiologies, including phantom pain after amputation [45]. In regards to pain after stroke, DBS reveals greatest efficacy for stroke patients complaining of burning hyperaesthesia [18].…”
Section: Issn: 2373-8995mentioning
confidence: 99%